1993
DOI: 10.1111/j.1365-294x.1993.tb00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Native oak chloroplasts reveal an ancient divide across Europe

Abstract: Glacial refugia and postglacial migration are major factors responsible for the present patterns of genetic variation we see in natural populations. Traditionally postglacial history has been inferred from fossil data, but new molecular techniques permit historical information to be gleaned from present populations. The chloroplast tRNA(Leu1) intron contains regions which have been highly conserved over a billion years of chloroplast evolution. Surprisingly, in one of these regions which has remained invariant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
138
1
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 18 publications
10
138
1
1
Order By: Relevance
“…The relatively high rate of mutation through rearrangement in the mitochondrial genome means that intraspecific variation is sufficient for recent genetic divergence events, occurring over the period of a single glaciation, to be studied. This contrasts with the situation for chloroplast DNA where mutation rates are generally much lower and long periods of genetic isolation, amounting to many cycles of glaciation and deglaciation, may be needed for cpDNA divergence to accumulate between refugial populations (Ferris et al, 1993;Petit et al, 1993b). However, mtDNA analysis in plants cannot give the powerful phylogenetic perspective on population history provided by analysis of cpDNA (Demesure et al, 1996;van Dijk & Bakx-Schotman, 1997).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The relatively high rate of mutation through rearrangement in the mitochondrial genome means that intraspecific variation is sufficient for recent genetic divergence events, occurring over the period of a single glaciation, to be studied. This contrasts with the situation for chloroplast DNA where mutation rates are generally much lower and long periods of genetic isolation, amounting to many cycles of glaciation and deglaciation, may be needed for cpDNA divergence to accumulate between refugial populations (Ferris et al, 1993;Petit et al, 1993b). However, mtDNA analysis in plants cannot give the powerful phylogenetic perspective on population history provided by analysis of cpDNA (Demesure et al, 1996;van Dijk & Bakx-Schotman, 1997).…”
Section: Discussionmentioning
confidence: 65%
“…In these circumstances additional information may be gained by studying the distribution of genetic variation in present-day populations. Elements of genetic structure established at the time of invasion may remain and provide evidence for or against current interpretations of postglacial history (Ferris et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Locally, mountains and seas acted as signiWcant barriers, isolating populations in diVerent glacial refugia and constraining post-glacial migration routes (Hewitt, 1999;Taberlet et al, 1998). Temperate species, which presently occupy central and northern Europe, mainly derive from Mediterranean refugium populations that underwent range expansion in the late glacial and early post-glacial periods (Hewitt, 1996), with a western form deriving from an Iberian refugium and an eastern form from the Italo-Balkanic refugium (Dumolin-Lapegue et al, 1997;Ferris et al, 1993Ferris et al, , 1998Santucci et al, 1998;Thorpe, 1984). Several authors, however, suggest an additional mode of colonisation of central and northern Europe by non-Mediterranean populations, coming from one or more eastern refugia: Caucasus, southern Ural, central Europe, and western Asia (Bilton et al, 1998;Cooper et al, 1995;Michaux et al, 2004;Nesbo et al, 1999;Palme and Vendramin, 2002;Seddon et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These data summarize the results previously obtained with single-locus data (Zanetto & Kremer, 1995), and those obtained in the present study. Both emphasized the importance of the subdivision of the range of Q. petraea into three separated refugia during the last glaciation (Bennett et al, 1991), which have been confirmed by recent chloroplast DNA data (Ferris et a!., 1993;Petit et a!., 1993). The separation of the species lasted long enough so that these refugial populations became differentiated.…”
Section: Multiocus Population Differentiationmentioning
confidence: 71%
“…The actual east-west pattern of nuclear diversity in sessile oak stands has largely been shaped by the postglacial recolonization pathways, resulting in clinal variation of allele frequencies and zygotic disequilibria, as predicted by theoretical models (Feldman & Christiansen, 1975;Barbujani, 1988) and as illustrated by the geographical variation of the first canonical variate (Figs 4a, b). Furthermore, the absence of any sharp discontinuity along the longitudinal gradient suggests that the populations from the extremities of the natural range of the species have probably exchanged nuclear genes through pollen dispersion, whereas limits of seed dispersion from the original refugia were clearly delineated on the basis of chloroplast DNA data (Ferris et a!., 1993;Petit et a!., 1993). Finally, the important gene flow caused by pollen movement between differentiated original refugial populations has resulted in extremely low population differentiation (G = 2.5 per cent, Zanetto & Kremer, 1995), but still geographically organized along a continental gradient.…”
Section: Multiocus Population Differentiationmentioning
confidence: 99%